2D slowness visualization of ultrasonic wave propagation for delamination detection in CFRP laminates. (October 2022) - Saito, Osamu; Sen, Enhi; Okabe, Yoji
Abstract: Visualizing the propagation of Lamb waves generated by scanning laser injection is a promising and effective method for the nondestructive inspection of carbon fiber reinforced plastic (CFRP) structures. We evaluate the use of two-dimensional time-slowness maps of the acquired data for defect detection in CFRP laminates. The slowness maps can be constructed from the differences in wave propagation characteristics between two adjacent laser injection points. Using a CFRP plate, in which an artificial delamination is located at the center, we show that the delamination can be clearly observed as a hotspot in the two-dimensional slowness map. The visible hotspot is due to the dispersion of the lowest antisymmetric (A0 ) mode of the Lamb wave: the A0 mode slows down at the delaminated region. We also demonstrate that our method can be applied to an L-shaped structure. Two-dimensional slowness images can be useful for developing and applying practical inspection methods based on laser ultrasonic waves. Highlights: ・Defects in CFRP laminates are inspected using laser ultrasonic guided waves. ・A two-dimensional slowness map is made from the data obtained by scanning laser. ・The slowness map is simple and useful for defect detection.